Durable metabolic improvements 2 years after duodenal mucosal resurfacing (DMR) in patients with type 2 diabetes (REVITA-1 Study). (February 2022) - van Baar, Annieke C.G.; Devière, Jacques; Hopkins, David; Crenier, Laurent; Holleman, Frits; Galvão Neto, Manoel P.; Becerra, Pablo; Vignolo, Paulina; Rodriguez Grunert, Leonardo; Mingrone, Geltrude; Costamagna, Guido; Nieuwdorp, Max; et al.
Highlights: We demonstrate long-term safety and tolerability of DMR in patients with T2D. HbA1c was significantly reduced at 24 months post-DMR. Over 50% of patients reduced or kept their glucose lowering medications constant. Insulin resistance, a known pathological driver of T2D, improved after single DMR. We observed additional positive effects on metabolic disturbances in T2D post-DMR. Abstract: Aims: Duodenal mucosal resurfacing (DMR) is an endoscopic procedure developed to improve metabolic parameters and restore insulin sensitivity in patients with diabetes. Here we report long-term DMR safety and efficacy from the REVITA-1 study. Materials and Methods: REVITA-1 was a prospective, single-arm, open-label, multicenter study of DMR feasibility, safety, and efficacy in patients with type 2 diabetes (hemoglobin A1c [HbA1c] of 7.5–10.0% (58–86 mmol/mol)) on oral medication. Safety and glycemic (HbA1c), hepatic (alanine aminotransferase [ALT]), and cardiovascular (HDL, triglyceride [TG]/HDL ratio) efficacy parameters were assessed ( P values presented for LS mean change). Results: Mean ± SD HbA1c levels reduced from 8.5 ± 0.7% (69.1 ± 7.1 mmol/mol) at baseline ( N = 34) to 7.5 ± 0.8% (58.9 ± 8.8 mmol/mol) at 6 months ( P < 0.001); and this reduction was sustained through 24 months post-DMR (7.5 ± 1.1% [59.0 ± 12.3 mmol/mol], P < 0.001) while in greater than 50% of patients, glucose-lowering therapy was reduced or unchanged. ALT decreased from 38.1 ± 21.1 U/L at baseline to 32.5 ± 22.1 U/L at 24 months ( P = 0.048). HDL and TG/HDL improved during 24-months of follow-up. No device- or procedure-related serious adverse events, unanticipated device effects, or hypoglycemic events were noted between 12 and 24 months post-DMR. Conclusions: DMR is associated with durable improvements in insulin sensitivity and multiple downstream metabolic parameters through 24 months post-treatment in type 2 diabetes. Clinical trial reg. no. NCT02413567, clinicaltrials.gov.